Effects of live versus heat-killed probiotics on acute diarrhea in young children - Atik Indriyani; Mohammad Juffrie; Amalia Setyati (Indonesian Pediatric Society Publishing House, 2012)
Background Diarrhea remains one of the major causes of morbidity and mortality in children in developing countries. Probiotics have been shown to be beneficial for decreasing the frequency and duration of diarrhea. However, the reported effects on reducing the duration of diarrhea have been varied. Objective To compare the effectiveness of live and heat􀁂killed probiotics in 6􀁂60 month􀁂old children with acute diarrhea for decreasing duration and frequency of diarrhea and improving weight gain. Methods We conducted a randomized, single􀁂blind, controlled trial in children aged 6􀁂60 months with acute diarrhea. Children were randomized into two groups, receiving either live or heat􀁂 killed probiotics. All children received standard treatment for diarrhea and probiotics as adjuvant treatment. The primary outcomes were duration and frequency of diarrhea, as well as weight gain. T􀁂test was used for data analysis. Results There were 165 children with acute diarrhea enrolled in this study. They were divided into 2 groups, with 83 children receiving live probiotics and 82 children receiving heat􀁂killed probiotics. There were no significant differences in diarrheal duration in the two groups. The mean durations of diarrhea in the live and heat􀁂killed probiotic groups were 3.64 (SD 0.85) days and 3.74 (SD 0.73) days (P>0.05), respectively. Mean diarrheal frequencies were also not significantly different, with 3.25 (SD 1.44) times per day in the live probiotic group and 3.26 (SD 1.20) times per day in the heat􀁂killed probiotic group (P>0.05). In addition, mean weight gain was not significantly different, 'With 241.57 (SD 75.84) g in the live prohiotic group and 221.95 (SD 85.38) g in the heat-killed prohiotic group (P>0.05). Conclusion There were no significant differences between live and heat􀁂killed probiotics for reducing duration and frequency of diarrhea, as well as in weight gain in children aged 6􀁂60 months 'With acute diarrhea. [paediatr lndones. 2012;52:249-54].